Transesterification of cyclic carbonates with methanol at ambient conditions over tungstate-based solid catalysts - Sankar, M.; Nair, C. Madhavan; Murty, K. V. G. K.; Manikandan, Palanichamy (Applied Catalysis A-General, 2006)
Dimethyl carbonate synthesis with 80 mol% yield is achieved through transesterification of ethylene carbonate with methanol at ambient conditions (RT and atmospheric pressure) using alkali and alkaline-earth tungstates as solid catalysts. The catalysts are efficient even at the sub-ambient temperatures. Reactions under CO2 pressure indicate that CO2 atmosphere retards the transesterification reaction completely below 100 degrees C. Experimental conditions of 150 degrees C and 3.4 MPa CO2 pressure are required to obtain maximum DMC yield of 71 mol%. Synthesis of DMC by one-pot synthesis using epoxide, CO2 and methanol is not as effective as that by two-step method with the present catalyst system. Raman and IR spectra of methanol-interacting tungstates indicate the formation of a methoxide ion species adsorbed at the catalyst surface as one possible reaction intermediates. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Dimethyl carbonate; ethylene carbonate; heterogeneous catalyst; Raman spectroscopy; sodium tungstate; transesterification

Immobilization of phosphotungstic acid (PTA) on imidazole functionalized silica: evidence for the nature of PTA binding by solid state NMR and reaction studies - Sofia, L. T. Aany; Krishnan, Asha; Sankar, M.; Raj, N. K. Kala; Manikandan, Palanichamy; Rajamohanan, P. R.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry C, 2009)
Phosphotungstic acid (PTA) immobilized onto imidazole functionalized fumed silica and was used its an efficient catalyst for epoxidation of a variety of olefins using aqueous H(2)O(2) as all oxidant. Negligible leaching of PTA under the reaction conditions employed indicates a strong interaction between PTA and imidazole The immobilized catalysts Could be separated and reused after the catalytic cycle Evidence for the heterogenization of PTA oil the imidazole functionalized fumed silica has been inferred from different spectroscopic techniques like IR, UV-vis, and NMR. Importantly, the nature of binding of PTA oil the support has been studied in detail by solid state NMR spectroscopy using (15)N labeled imidazole Support. It is clear from the NMR Studies that the effective heterogenization of PTA is mainly due to imidazolium ion Formation oil the support by the acidic protons of PTA and the resultant ion pair

Facile synthesis of β-functionalized “push-pull” Zn(II) porphyrins for DSSC applications - Prakash, K. (Dyes and Pigments, 2017)
Three new β-substituted “push-pull” Zn(II) porphyrin dyes with various electron donors at meso-positions and cyanoacetic acid as acceptor at β-position have been designed and synthesized. These porphyrins have been characterized by UV-Vis, Fluorescence, 1H NMR and 13C NMR spectroscopic techniques and cyclic voltammetric studies. The Soret and Q band of Zn(II) porphyrin dyes were found to be red-shifted (30–35 nm) as compared to ZnTPP. The fluorescence quenching and the decrement in quantum yield and lifetime suggest intramolecular charge transfer from donor to acceptor. Zn porphyrins exhibited anodic shift in their first redox potentials (0.03–0.11 V) as compared to ZnTPP. The HOMO-LUMO energy levels of Zn porphyrin dyes were compared with the conduction band of TiO2 and the electrolyte I−/I3 −. The HOMO levels of all the dyes are sufficiently higher than the energy level of electrolyte I−/I3 − and LUMO levels significantly lower than the conduction band of TiO2 which reflect the feasibility of facile electron-transfer. ZnT(Mes)P(CN-COOH) has been co-sensitized with N719 dye to further improve the PCE efficiency. These dyes displayed power conversion efficiency (PCE) of η = 1.72–3.13% where co-sensitized ZnT(Mes)P(CN-COOH) (N719) dye demonstrated maximum PCE efficiency up to 5.35%, with a Jsc of 11.8 mA cm−2, a Voc of 630 mV and a fill factor (FF) of 72% due to better light harvesting capacity.
Keywords: charge transfer; Conduction Bands; Cyanoacetic Acid; Electrolytes; Floorescence; Redox Reaction; zinc compounds